2011
DOI: 10.1073/pnas.1114573108
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygote advantage as a natural consequence of adaptation in diploids

Abstract: Molecular adaptation is typically assumed to proceed by sequential fixation of beneficial mutations. In diploids, this picture presupposes that for most adaptive mutations, the homozygotes have a higher fitness than the heterozygotes. Here, we show that contrary to this expectation, a substantial proportion of adaptive mutations should display heterozygote advantage. This feature of adaptation in diploids emerges naturally from the primary importance of the fitness of heterozygotes for the invasion of new adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
204
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(215 citation statements)
references
References 46 publications
7
204
0
4
Order By: Relevance
“…Sellis et al (2011) showed that, among loci contributing to adaptive evolutionary change, the probability of heterozygote advantage tends to increase with the "standardized size" (Orr 1998) of adaptive mutations. Under Fisher's original scaling, mutation size is given by x ¼ r ffiffiffi n p =ð2zÞ; where r is the absolute phenotypic effect size of the mutation, n is the number of traits, and z represents the displacement of the population from a fitness optimum within phenotypic space (see Fisher 1930, pp.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Sellis et al (2011) showed that, among loci contributing to adaptive evolutionary change, the probability of heterozygote advantage tends to increase with the "standardized size" (Orr 1998) of adaptive mutations. Under Fisher's original scaling, mutation size is given by x ¼ r ffiffiffi n p =ð2zÞ; where r is the absolute phenotypic effect size of the mutation, n is the number of traits, and z represents the displacement of the population from a fitness optimum within phenotypic space (see Fisher 1930, pp.…”
mentioning
confidence: 99%
“…However, most theory cannot predict the probability of balancing selection because it does not incorporate details of the fitness effect distribution among random alleles and genotypes in a population. Such details ultimately determine the relative likelihood of different forms of selection at individual loci.A recent study by Sellis et al (2011) provides new insight into the probability of balancing selection by modeling the (Fisher 1930; Orr 2005a,b)-an influential theoretical framework for the fitness effect distribution of random mutations. Sellis et al (2011) showed that, among loci contributing to adaptive evolutionary change, the probability of heterozygote advantage tends to increase with the "standardized size" (Orr 1998) of adaptive mutations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, heterosis has been postulated for several other variations in common genetic diseases, e.g., malaria, and has been postulated to be a natural consequence of adaption in diploids [26,27]. Regarding the inflammatory response, heterozygosity of the mannose binding lectin genotype predicts an advantage to fatal outcome of sepsis patients [28].…”
Section: Discussionmentioning
confidence: 99%